(untitled) (Sebha University Conference Proceedings, 2025)
This paper presents a comprehensive study on the design and optimization of Multi-Degree-of-Freedom (MDOF) vibration isolation systems using MATLAB. Vibration isolation is crucial in various engineering applications to protect sensitive equipment from external vibrations. The focus is on developing an optimized design methodology that balances performance metrics such as isolation efficiency, frequency response, and practical implementation considerations. The MATLAB environment is utilized for simulation, analysis, and optimization, leveraging its powerful computational capabilities and toolboxes for multidimensional system modeling. The paper discusses theoretical foundations, design parameters, optimization techniques, and simulation results to demonstrate the effectiveness of the proposed methodology in achieving enhanced vibration isolation performance.